Factor Analysis of The High Prevalence of Child Marriage in West Sulawesi - Asma Amin; Andi Nur Fiqi Utami; Dian Pertiwi; Salmiati Salmiati; Ervi Alfryanti; Nur Wahida (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2024)
From 2008 to 2015, West Sulawesi persistently recorded the highest prevalence of child marriage in Indonesia, peaking at 34.22 percent in 2015, a figure markedly higher than the national average of 22.82 percent. This study employs a qualitative methodology to unravel the underlying factors contributing to the rampant occurrence of child marriage in this region. The research encompasses three distinct approaches: in-depth interviews, thorough document-based analysis, and comprehensive internet-based investigation. The findings reveal three principal factors driving the high prevalence of child marriage in West Sulawesi: cultural values and traditions, legal loopholes pertaining to marriage dispensation, and parental knowledge and education. (1) Cultural Values and Traditions refer to the enduring influence of Siri culture, which encourages inter-family marriages, and the persistent Tisaka tradition, which enforces marriages as a consequence of violating social mores, play significant roles. Additionally, the siballi parri culture, which advocates for shared responsibilities between spouses, extends to children. In this context, marrying off children is seen as a means to alleviate the parental burden, as the wife transitions to the husband's responsibility. Moreover, there exists a particular interpretation of Islam that endorses child marriage. (2) Legal Loopholes means the existence of marriage dispensation serves as a legal concession, allowing marriages that do not meet the statutory requirements of the positive law. (3) Parental Knowledge and Education refer to the limited awareness among parents regarding the legal age for marriage and reproductive health education. Parental Knowledge and Education means a critical factor is the limited awareness among parents regarding the legal age for marriage and reproductive health education.